2002
DOI: 10.1207/s15516709cog2601_2
|View full text |Cite
|
Sign up to set email alerts
|

Memory for goals: an activation‐based model

Abstract: Goal-directed cognition is often discussed in terms of specialized memory structures like the "goal stack." The goal-activation model presented here analyzes goal-directed cognition in terms of the general memory constructs of activation and associative priming. The model embodies three predictive constraints: (1) the interference level, which arises from residual memory for old goals; (1) the strengthening constraint, which makes predictions about time to encode a new goal; and (3) the priming constraint, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
740
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(788 citation statements)
references
References 66 publications
42
740
4
2
Order By: Relevance
“…In the present experiment, we cannot rule out the possibility that the demonstrated intention-superiority effect reflects strategic rehearsal processes (Altmann & Trafton, 2002). The memory task was announced 3 s before the first recognition trial started.…”
Section: Discussionmentioning
confidence: 78%
“…In the present experiment, we cannot rule out the possibility that the demonstrated intention-superiority effect reflects strategic rehearsal processes (Altmann & Trafton, 2002). The memory task was announced 3 s before the first recognition trial started.…”
Section: Discussionmentioning
confidence: 78%
“…Abstracting from the underlying memory mechanics, Altmann and Trafton (2002) have proposed a general cognitive framework for modeling the effects of interruptions on tasks and associated problem state. Memory for goals is an activation-based approach for memory that builds on the ACT-R cognitive framework (Anderson et al 2004).…”
Section: Memorymentioning
confidence: 99%
“…Recent research has demonstrated strong connection between the availability of environmental cues and reduced resumption costs (Altmann and Trafton 2002;Hodgetts and Jones 2006;Trafton et al 2005). Conversely, if the cue is removed or tampered with, this benefit is removed.…”
Section: Environmental Cuesmentioning
confidence: 99%
“…Research has proven that disrupted activities increase error rates (Altmann & Trafton, 2002;Bailey & Konstan, 2006;Cellier & Eyrolle, 1992;Jones et al, 1990). A number of studies have found that interrupted activities are correlated with task degradation and impaired cognitive performance (Adler & Benbunan-Fich, 2012;Banbury et al, 2001;Fox, Rosen, & Crawford, 2009;NavehBenjamin, Craik, Perretta, & Tonev, 2000;Ophir et al, 2009;Wang et al, 2012).…”
Section: Multitasking In the Workplacementioning
confidence: 99%